Identification of key genes associated with mesocotyl length through a genome-wide association study in rice - Xue, Li; Wang, Sen; Zhang, Qiuyu; Han, Bing; Cui, Di; Han, Longzhi; Deng, Jianxin; Ma, Xiaoding (Frontiers in Plant Science, 2025)
Mesocotyl length is a key trait affecting seedling emergence and establishment in dry direct-seeded rice, with longer mesocotyls promoting rapid and uniform emergence, thereby forming larger effective populations. Therefore, mining genes associated with mesocotyl length will facilitate the development of rice varieties suitable for dry direct seeding. In this study, 300 rice germplasm resources with a wide range of sources were selected as experimental materials. Phenotypic traits such as mesocotyl length and seedling emergence rate were systematically determined in each variety by setting different mulch depth treatments. Genome-wide association analysis (GWAS) was used to locate QTL controlling mesocotyl length and predict candidate genes. The results showed that mesocotyl length increased significantly with greater soil cover depth, while excessively deep sowing treatments inhibited seedling emergence. The GWAS analysis identified four QTLs associated with mesocotyl length and two QTLs associated with seedling emergence, with phenotypic contributions of 6.96-8.48%. Among them, the mesocotyl length-related QTL qML3 located at 28.03-28.43 Mb on chromosome 3 was detected at both sowing depths. Gene annotation analysis identified nine candidate genes related to plant hormones and transcription factors for qML3. Further investigation revealed three genes (LOC_Os03g49250, LOC_Os03g49400, and LOC_Os03g49510) exhibiting distinct haplotypes with significant differences in mesocotyl length, suggesting they may be causal genes for qML3. The results provide new clues to elucidate the molecular mechanism of rice mesocotyl development and lay an important foundation for subsequent gene function verification and molecular breeding. In the future, the functions of these candidate genes will be verified by transgenic and other methods, and molecular markers will be developed for genetic improvement of drought-tolerant rice varieties.